Outcomes of Intertrochanteric Fractures in Patients Managed with Proximal Femoral Nail Antirotation - Sardar Sohail Afsar, Akbar Ali, Yaqoob Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The older population is quite susceptible to intertrochanteric fractures. These fractures generally affect elderly patients with several medical conditions and eventually result in the patient losing their functional independence. Different treatment modalities are used for the management of proximal femoral fractures.s Objective: Outcomes of intertrochanteric fractures in patients managed with Proximal Femoral Nail Antirotation Methodology: The current study was descriptive study carried out at the orthopedic department, Qazi Hussain Ahmad Medical College, Nowshera from June 2021 to June 2022. All the enrolled patients were operated under an image intensifier by Proximal Femoral Nail Antirotation. Consultations after surgery were planned every two weeks for the first month, and then every month for the next six months. Radiographs were used to evaluate the radiological union at each visit. The functional outcome was determined with Harris Hip Score. SPSS version 23 was used to enter and analyze all of the data. Results: In the current study, totally 40 patients with intertrochanteric fractures were enrolled. The male participants in this study were 12 (30%) while female patients were 28 (70%). In all of our enrolled patients, radiological union occurs in a mean (SD) duration of 14.9 (2) weeks. The functional outcome in our study, based on Harris Hip Score was excellent in 12 (30%) patients, good in 18 (45%), fair in 8 (20%) patients and poor in 2 (5%) patients. Conclusion: Our study concludes that management of intertrochanteric fractures with proximal femoral nail antirotation is an effective procedure for excellent and good functional outcomes and less post-operative complication. Keywords: intertrochanteric fractures; Proximal Femoral Nail Antirotation; functional outcomes